Karakteristik Santri sebagai Faktor Risiko Timbulnya Gejala Skabies di Pondok Pesantren Salafiyah Kabupaten Banyuwangi - Zulaikha, Putri Namira; Nur, Ardiati Fatma; Adriyani, Retno (Media Gizi Kesmas, 2024)
Background: Scabies is a skin disease that is easily transmitted when in close skin contact with sufferers for a long time. This disease is often found in densely populated places, one of which is in Islamic boarding schools. Objectives: This study aimed to analyze the risk factors associated with the characteristics of students with the incidence of scabies symptoms at the Salafiyah Islamic Boarding School, Banyuwangi Regency. Methods: This research was an observational study with a cross-sectional design. The research population consisted of all students in the Salafiyah Islamic Boarding School, Banyuwangi totaling 191 students. The sample size was 63 students by simple random sampling. Data collection was carried out online using a google form. Data analysis using chi-square test with α = 0,05. Results: The results showed that 42.9% of students had symptoms of scabies and found that two factors were statistically related to scabies symptoms in students, namely history of lived in other Islamic boarding schools (p=0.026) and history of preceding scabies (p=0.000). While the characteristics of age (p=0.380), gender (p=0.680), level of education (p=0.156), and length of stay in Islamic boarding schools (p=0.537) did not show a significant relationship with scabies symptoms in students. Conclusions: The history of living in other Islamic boarding schools and the history of preceding scabies statistically showed a significant relationship to the symptoms of scabies in students at Salafiyah Islamic Boarding School in Banyuwangi.